A new species of the genus Rhabdomiris (Hemiptera: Heteroptera: Miridae: Mirinae) from the Korean Peninsula, based on morphology and molecular data - Kim, Junggon; Kim, Young Jin; Lim, Jongok; Jung, Sunghoon (Zootaxa, 2019)
A new species, Rhabdomiris koreanus sp. nov. is described from the Korean Peninsula based on morphology and molecular data. At the same time, a correction of the erroneous record of R. striatellus in the Korean fauna is proposed. Morphological information including a diagnosis and description of the genitalia and biological notes for each species within Rhabdomiris are provided with photographs. A key to the Rhabdomiris species is also presented.